2019
DOI: 10.3389/fimmu.2019.01806
|View full text |Cite
|
Sign up to set email alerts
|

CIITA-Driven MHC Class II Expressing Tumor Cells as Antigen Presenting Cell Performers: Toward the Construction of an Optimal Anti-tumor Vaccine

Abstract: Construction of an optimal vaccine against tumors relies on the availability of appropriate tumor-specific antigens capable to stimulate CD4+ T helper cells (TH) and CD8+ cytolytic T cells (CTL). CTL are considered the major effectors of the anti-tumor adaptive immune response as they recognize antigens presented on MHC class I (MHC-I) molecules usually expressed in all cells and thus also in tumors. However, attempts to translate in clinics vaccination protocols based only on tumor-specific MHC-I-bound peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 60 publications
3
67
0
Order By: Relevance
“…Several studies have observed that some of these genes play important roles in the regulation of the immune response. For example, CIITA can trigger antitumor immunity by inducing the expression of the MHC class II molecules of tumor cells, CD3D can regulate the proliferation and development of T cells, and GNLY can encode granulysin, which can cause the lysis of tumor cells . Interestingly, using the median TIM score as a cutoff value, we observed that the genes of patients with high TIM scores were enriched in protumor pathways and that the genes of patients with low TIM scores were enriched in inflammatory pathways.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have observed that some of these genes play important roles in the regulation of the immune response. For example, CIITA can trigger antitumor immunity by inducing the expression of the MHC class II molecules of tumor cells, CD3D can regulate the proliferation and development of T cells, and GNLY can encode granulysin, which can cause the lysis of tumor cells . Interestingly, using the median TIM score as a cutoff value, we observed that the genes of patients with high TIM scores were enriched in protumor pathways and that the genes of patients with low TIM scores were enriched in inflammatory pathways.…”
Section: Discussionmentioning
confidence: 90%
“…Adoptive transfer methods are based on patientderived lymphocytes that are expanded, genetically modified, or activated ex vivo before being reinfused (Robbins et al, 2015;Lu et al, 2017). In addition, the application of antitumor vaccination approaches have made considerable progress in recent years (reviewed in Rammensee and Singh-Jasuja, 2013;Accolla et al, 2019;Peng et al, 2019). The method most widely established in the clinic is the treatment with checkpoint inhibitors.…”
Section: Effects Of the Ecm On Immunotherapymentioning
confidence: 99%
“…The most critical TFs were CIITA, BATF, VDR, and CBX2. Among them, CIITA has been shown to drive MHC Class II expressing tumor cells as professional antigen presenting cell (APC) performers, thus activating the immune cells and constructing the speci c optimal anti-tumor vaccine [13]. BATF can induce the T cell exhaustion during chronic infection, which is characterized by expression of inhibitory receptors and protect cells from excessive immunopathology [14,15].…”
Section: Discussionmentioning
confidence: 99%